Point-Contact Spectroscopy - Naidyuk, Yu.G; Yanson, I.K (Springer Series in Solid-State Sciences, 2005)
A new type of spectroscopy, Point-Contact Spectroscopy, was created for the study of conduction electron interaction mechanism with a class of elementary excitations in solids. The goal of this book is to introduce readers to Point Contact Spectroscopy. The physical principles of spectroscopy of quasi-particle excitations in metals at low temperatures by means of point contacts are presented. The point contact constitutes a tiny metallic bridge connecting bulk electrodes. Along with the most thoroughly studied phonon excitations, the interaction of electrons with other quasiparticles (magnons, crystal-field electron excitations, paramagnetic impurities, two-level systems, etc), are reviewed. Various experimental techniques for point contact production are described. Examples of point-contact spectra are presented for pure metals, alloys and compounds, as well as for semimetals and semiconductors, high-Tc and other exotic superconductors, heavy fermion systems, Kondo-lattices, mixed valence compounds and more. Special attention is paid to contact conductance behavior in superconducting states, in high magnetic fields and under high-frequency radiation. The theoretical part of the book is restricted to presenting the main relations without superfluous details. Point-Contact Spectroscopy includes more than 200 figures.